2008
DOI: 10.1111/j.1471-4159.2008.05412.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of non‐steroid anti‐inflammatory drugs action on ASICs expressed in hippocampal interneurons

Abstract: The inhibitory action of non‐steroid anti‐inflammatory drugs was investigated on acid‐sensing ionic channels (ASIC) in isolated hippocampal interneurons and on recombinant ASICs expressed in Chinese hamster ovary (CHO) cells. Diclofenac and ibuprofen inhibited proton‐induced currents in hippocampal interneurons (IC50 were 622 ± 34 μM and 3.42 ± 0.50 mM, respectively). This non‐competitive effect was fast and fully reversible for both drugs. Aspirin and salicylic acid at 500 μM were ineffective. Diclofenac and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 59 publications
(67 reference statements)
5
48
0
2
Order By: Relevance
“…Inflammation induces a large increase in ASIC mRNA levels in DRGs, which is prevented by administration of the nonsteroidal anti-inflammatory drugs (NSAIDs) aspirin, diclofenac, and ibuprofen at therapeutic doses (Voilley et al, 2001). In addition, ASIC currents are inhibited by NSAIDs with IC 50 values in the order of hundreds of micromolars to several millimolars (Voilley et al, 2001;Dorofeeva et al, 2008), thus with 100-to 1000-fold lower potency than the inhibition of cyclooxygenases by these drugs (Warner et al, 1999). It is therefore likely that the inhibition of ASIC expression, but not the experimentally observed inhibition of ASIC currents, may contribute to the clinical effects of NSAIDs.…”
Section: Pharmacologymentioning
confidence: 99%
“…Inflammation induces a large increase in ASIC mRNA levels in DRGs, which is prevented by administration of the nonsteroidal anti-inflammatory drugs (NSAIDs) aspirin, diclofenac, and ibuprofen at therapeutic doses (Voilley et al, 2001). In addition, ASIC currents are inhibited by NSAIDs with IC 50 values in the order of hundreds of micromolars to several millimolars (Voilley et al, 2001;Dorofeeva et al, 2008), thus with 100-to 1000-fold lower potency than the inhibition of cyclooxygenases by these drugs (Warner et al, 1999). It is therefore likely that the inhibition of ASIC expression, but not the experimentally observed inhibition of ASIC currents, may contribute to the clinical effects of NSAIDs.…”
Section: Pharmacologymentioning
confidence: 99%
“…Previous studies demonstrated that nonsteroidal anti-inflammatory drugs (NSAIDs) significantly inhibited ASIC currents in hippocampus and sensory neurons (30,31). To investigate the effect of NSAIDs on ASICs in iDCs, the responses of ASIC currents to NSAIDs (ibuprofen or diclofenac) were tested.…”
Section: Nonsteroidal Anti-inflammatory Drugs Suppress Inward Asic Cumentioning
confidence: 99%
“…However, the study by Dorofeeva et al (2008) showed that 0.5 mM aspirin and salicylate has no significant effect on the ASIC current in cultured hippocampal neurons. In this study, we found that high doses of salicylate and aspirin exerted partial inhibition on ASICs in the cultured cerebral cortical neuron.…”
Section: Discussion Inhibitory Effects Of Millimolar Salicylate and Amentioning
confidence: 93%
“…In this study, we found that high doses of salicylate and aspirin exerted partial inhibition on ASICs in the cultured cerebral cortical neuron. We address the difference as follows: 1) the concentration of salicylate and aspirin used in the study by Dorofeeva et al was 0.5 mM (Dorofeeva et al, 2008), whereas in this study the concentration that produced significant inhibition was above 1 mM; 2) the regions we examined in this study are the cortex, for which no reports have described the effects of salicylate and aspirin on ASICs to date. In addition to ASIC1a, ASIC2a, and ASIC2b, our recent study has indicated that ASIC3 is present in the cortex of the rat (Biagini et al, 2001;Alvarez de la Rosa et al, 2003;Meng et al, 2009).…”
Section: Discussion Inhibitory Effects Of Millimolar Salicylate and Amentioning
confidence: 96%